Phenotyping and QTL mapping for cold tolerance at the germination and seedling stages in Argentine temperate rice - Bonell, Martha Lucrecia; Arguissain, Gustavo Gabriel; Crepy, Maria Andrea; Fernandez, Paula Del Carmen; Heinz, Ruth Amelia (Springer, 2020)
In Argentina, the yield potential of rice (Oryza sativa L.) under suboptimal temperatures of temperate regions and during early sowing in tropical regions depends on its low-temperature germinability (LTG) and subsequent cold tolerance at the seedling stage (CTS). This study focused on the phenotyping and identification of contrasting henotypes for LTG and CTS of 18 rice genotypes genotyped with 49 markers previously linked to cold tolerance. The selected markers revealed phenotypic variability among the genotypes evaluated. The results also demonstrated that both traits are regulated by different genes and that CTS is associated with differential alleles of candidate gene (CG)-based markers. Biplot clustering analysis allowed the selection of two cultivars, H298a/90 and Puitá INTA CL, contrasting for LTG, CTS and CG alleles. An F2 population (n = 128) derived from these two cultivars was genotyped with 43 SSR- and CG-based markers and 89 F2:3 families (~ 1800 seedlings) phenotyped for CTS. Single-marker analysis detected two major QTL that had been previously reported for CTS: qCTS11, which explained 18.35% of the phenotypic variance at 7 days of treatment, and qCTS12, which explained 26.62% and 47.94% of the phenotypic variance at 7 and 14 days of treatment, respectively. Marker-assisted introgression of QTL alleles favorable for CTS into Puitá INTA CL, which has high LTG, could contribute to obtaining breeding lines with early seedling vigor adapted to the sowing season in Argentina.